(untitled) (American Journal of Business Management, Economics and Banking, 2026)
The global banking system is actively implementing artificial intelligence technologies to combat money laundering and terrorist financing. This article presents a systematic analysis of international experience in applying AI technologies in AML systems of leading global banks and financial institutions of CIS countries. Cases of HSBC, JPMorgan Chase, Standard Chartered, Deutsche Bank, and Citibank demonstrating specific measurable implementation outcomes are analysed. Special attention is devoted to the state of AI adoption in the banking sectors of Russia, Kazakhstan, and other CIS countries, including a detailed analysis of Sberbank’s experience. Critical limitations of traditional financial monitoring systems and the advantages of AI-based solutions are identified. Federated learning technology is examined as an innovative approach to interbank cooperation that does not require the disclosure of confidential client data.